Development and Evaluation of a Gamified Mathematical Mobile Application in Learning Integer Operations - Castro, Jeneline (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study developed and evaluated a gamified mathematical mobile application designed to improve Grade 8 students’ understanding of integer operations. The study was anchored on constructivism, behaviorism, cognitivism, Self-Determination Theory, Flow Theory, the Technology Acceptance Model, and the TPACK framework, which collectively emphasized learner engagement, motivation, scaffolding, feedback, and technology integration in mathematics education. A quasi-experimental one-group pretest-posttest design combined with a Research and Development (R&D) approach was employed. The study involved approximately 40 Grade 8 students from D.T. Durano Memorial Integrated School in Danao City, Cebu during the School Year 2025–2026. Data were gathered using a paper-and-pencil pretest, an in-app posttest, and an expert-validated questionnaire based on the Technology Acceptance Model. Descriptive statistics, weighted mean, and paired sample t-test were utilized to analyze the gathered data. The findings revealed that the gamified mathematical mobile application received highly favorable evaluations in terms of user interface, gamification features, instructional content, interactivity and feedback, and visual and audio components. Students demonstrated improved performance in integer operations after using the application, with significant differences observed between pretest and posttest scores across easy, average, and difficult levels. Learners also perceived the application as useful, engaging, and easy to use, indicating strong acceptability and positive attitudes toward mobile-based mathematics learning. Although actual usage remained moderate, the application effectively functioned as a supplementary instructional tool that enhanced students’ motivation, participation, comprehension, and problem-solving skills in integer operations. The study concluded that the gamified mathematical mobile application is an effective and acceptable learning intervention for Grade 8 mathematics instruction. The study supports Sustainable Development Goal 4 (Quality Education) through the promotion of innovative and technology-based instructional strategies and Sustainable Development Goal 9 (Industry, Innovation and Infrastructure) through the integration of digital learning technologies in education. The research contributes to educational and technological sustainability by encouraging learner-centered instruction, strengthening digital learning environments, and supporting the continuous integration of mobile learning applications in mathematics education.
Keywords: Constructivism; Gamification; Integer Operations; Mathematics Education; Mobile Learning; Technology Acceptance Model; User Engagement